Recall Bias in Retrospective Assessment of Preoperative Patient-Reported American Shoulder and Elbow Surgeons Scores in Arthroscopic Rotator Cuff Repair Surgery. Issue 6 (May 2020) - Gotlin, Matthew J.; Kingery, Matthew T.; Baron, Samuel L.; McCafferty, Joseph; Jazrawi, Laith M.; Meislin, Robert J.
Background: The gold-standard method for collecting patient-reported outcomes (PROs) is the prospective assessment of preoperative to postoperative change. However, this method is not always feasible because of unforeseen cases or emergencies, logistical and infrastructure barriers, and cost issues. In such cases, a retrospective approach serves as a potential alternative, but there are conflicting conclusions regarding the reliability of the recalled preoperative PROs after orthopaedic procedures. Purpose: To assess the agreement between prospectively and retrospectively collected PROs for a common, low-risk procedure. Study Design: Cohort study (Diagnosis); Level of evidence, 3. Methods: Patients who underwent arthroscopic rotator cuff repair between May 2012 and September 2017 at the study institution were identified. All of the patients completed the American Shoulder and Elbow Surgeons (ASES) Standard Shoulder Assessment Form preoperatively at their preassessment appointment. Patients were then contacted in the postoperative period and asked to recall their preoperative condition while completing another ASES form. Results: A total of 84 patients completed the telephone survey and were included in this analysis (mean age, 57.40 ± 9.96 years). The mean duration of time from onset of shoulder symptoms to surgery was 9.13 ± 9.08 months. The mean duration of time between surgery and recall ASES administration was 39.12 ± 17.37 months. The mean recall ASES score was significantly lower than the preoperative ASES score (30.69 ± 16.93 vs 51.42 ± 19.14; P < .001). There was poor test-retest reliability between preoperative ASES and recall ASES (intraclass correlation coefficient, 0.292; 95% CI, –0.07, 0.57; P = .068). Greater age at the time of recall, a shorter symptomatic period before surgery, and less severe preoperative shoulder dysfunction were associated with a greater difference between preoperative ASES and recall ASES. Conclusion: Retrospectively reported PROs are subject to significant recall bias. Recalled PROs were almost always lower than their prospectively recorded counterparts. Recalled PROs are more likely to be accurate when reported by younger patients, those with a longer duration of symptoms, and those with more severe preoperative conditions.